Transformations of rural housing patterns and their impact on th territory. The case of Ambato - Ecuador - Grijalva, María Susana (2020)
Today, both territorial transformations and morphological changes in rural spaces raise some questions that can only be understood from a historical and systemic view. Canton Ambato has its own dynamics that make it a unique space in the country, as it has an economic system anchored to a local history that shows a basic social organization and a strong artisan and industrial productivity. However, the advance of urban logics over rural spaces puts at risk the conservation of these dynamics through the loss of material heritage. This article aims to highlight the changes in the patterns of rural housing as well as other buildings and their progressive replacement by contemporary architectural codes and patterns that contribute to the process of destructuring rural spaces, as well as urban-rural articulations. Likewise, it is intended to make visible the alternatives that the actors have to preserve their cultural capital while building themselves as a society in the midst of an accelerated process of urbanization.